Chromosome‐level genome of Camellia lanceoleosa provides a valuable resource for understanding genome evolution and self‐incompatibility. (26th April 2022) - Gong, Wenfang; Xiao, Shixin; Wang, Linkai; Liao, Zhenyang; Chang, Yihong; Mo, Wenjuan; Hu, Guanxing; Li, Wenying; Zhao, Guang; Zhu, Huaguo; Hu, Xiaoming; Ji, Ke; et al.
SUMMARY: The section Oleifera (Theaceae) has attracted attention for the high levels of unsaturated fatty acids found in its seeds. Here, we report the chromosome‐scale genome of the sect. Oleifera using diploid wild Camellia lanceoleosa with a final size of 3.00 Gb and an N50 scaffold size of 186.43 Mb. Repetitive sequences accounted for 80.63% and were distributed unevenly across the genome. Camellia lanceoleosa underwent a whole‐genome duplication event approximately 65 million years ago (65 Mya), prior to the divergence of C .  lanceoleosa and Camellia sinensis (approx. 6–7 Mya). Syntenic comparisons of these two species elucidated the genomic rearrangement, appearing to be driven in part by the activity of transposable elements. The expanded and positively selected genes in C .  lanceoleosa were significantly enriched in oil biosynthesis, and the expansion of homomeric acetyl‐coenzyme A carboxylase ( ACCase ) genes and the seed‐biased expression of genes encoding heteromeric ACCase, diacylglycerol acyltransferase, glyceraldehyde‐3‐phosphate dehydrogenase and stearoyl‐ACP desaturase could be of primary importance for the high oil and oleic acid content found in C. lanceoleosa . Theanine and catechins were present in the leaves of C .  lanceoleosa . However, caffeine can not be dectected in the leaves but was abundant in the seeds and roots. The functional and transcriptional divergence of genes encoding SAM‐dependent N ‐methyltransferases may be associated with caffeine accumulation and distribution. Gene expression profiles, structural composition and chromosomal location suggest that the late‐acting self‐incompatibility of C. lanceoleosa is likely to have favoured a novel mechanism co‐occurring with gametophytic self‐incompatibility. This study provides valuable resources for quantitative and qualitative improvements and genome assembly of polyploid plants in sect. Oleifera . Significance Statement: Section  Oleifera in the genus Camellia attracts considerable attention because the seeds produce edible oils with abundant unsaturated fatty acids. Our study uncovered the genome information of sect. Oleifera with diploid wild Camellia lanceoleosa, elucidated the genomic rearrangement between C. lanceoleosa and Camellia sinensis, and performed analyses of oil biosynthesis, caffeine distribution and self‐incompatibility in C. lanceoleosa.